2000
DOI: 10.1124/mol.58.6.1502
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Antagonism of Recombinant P2X2/3Receptors by 2′,3′-O-(2,4,6-Trinitrophenyl) Adenosine 5′-Triphosphate (TNP-ATP)

Abstract: TNP-ATP has become widely recognized as a potent and selective P2X receptor antagonist, and is currently being used to discriminate between subtypes of P2X receptors in a variety of tissues. We have investigated the ability of TNP-ATP to inhibit ␣,␤-methylene ATP (␣,␤-meATP)-evoked responses in 1321N1 human astrocytoma cells expressing recombinant rat or human P2X 2/3 receptors. Pharmacological responses were measured using electrophysiological and calcium imaging techniques. TNP-ATP was a potent inhibitor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 32 publications
6
62
0
1
Order By: Relevance
“…5B). If TNP-ATP binds to the same site(s) as ATP, as is suggested for the homomeric P2X 3 receptor (Burgard et al, 2000) and for the homomeric P2X 2 receptor (Trujillo et al, 2006), then these results indicate that Lys 69 is involved in agonist binding.…”
Section: Partial Agonist Actions Of Suramin and Tnp-atp At P2x 2 [T339s]mentioning
confidence: 88%
“…5B). If TNP-ATP binds to the same site(s) as ATP, as is suggested for the homomeric P2X 3 receptor (Burgard et al, 2000) and for the homomeric P2X 2 receptor (Trujillo et al, 2006), then these results indicate that Lys 69 is involved in agonist binding.…”
Section: Partial Agonist Actions Of Suramin and Tnp-atp At P2x 2 [T339s]mentioning
confidence: 88%
“…The most potent competitive antagonist of P2X3 receptors is the 2′,3′-O-(2,4,6-trinitrophenyl)-ATP (TNP-ATP, Fig. 1) [47], with low nanomolar activity. In fact, this molecule showed to inhibit ATP or α,β-meATP evoked current at P2X3 receptors expressed by HEK293 cells with an IC 50 value of 2 nM [48].…”
Section: Introductionmentioning
confidence: 99%
“…bound to trinitrophenyl ATP (TNP-ATP), which is composed of ATP and a trinitrophenyl group attached to the 2′ and 3′ hydroxyl of the ribose moiety (Fig. S6A) and is reportedly a representative non-subtype-selective antagonist of P2X receptors that competes with ATP (10,(39)(40)(41). We confirmed that the ATP-evoked currents of ΔzfP2X 4 -A′ were inhibited by TNP-ATP and that TNP-ATP did not evoke currents in oocytes expressing ΔzfP2X 4 -A′ (Fig.…”
Section: Nmr Resonances From Methionine Residues Introduced In Thementioning
confidence: 99%